Application of value stream mapping using simulation to decrease production lead time: a Malaysian manufacturing case. (1st January 2011) - Esfandyari, Alireza; Osman, Mohd Rasid; Ismail, Napsiah; Tahriri, Farzad
Lean concept has been applied across many companies which offer value and eliminate wastes. Value stream map (VSM) as one of the fundamental tools in lean concept outlines the material and information flows for a product family to reduce wastes at discrete event production routine. In this paper, the improvement of the production lead time using VSM as a technique in a Malaysian supplier, with a job shop production system, is investigated. The main contribution of this paper is reducing production lead time when the Takt Time is much higher than the highest station's cycle time, and reducing unplanned released orders. This paper evaluates the present routing events using current state map and the future state is created answering the eight standard questions. Then, a detailed simulation model was developed to verify the result from future state map and answering the questions that are unable to be addressed by VSM.